Caribbean Confederations as Relationalities - Yolanda Martínez-San Miguel (Journal of French and Francophone Philosophy)
In this essay, I connect my work on Archipelago studies with Édouard Glissant’s notions of relationality and Caribbean confederations to formulate what I denominate as the erotics of archipelagic thinking. My main goal is to share my process of thinking with and through Glissant’s work to focus on a series of theoretical gestures that have allowed me to propose modes of reading literary depictions of Caribbean con/federations that go beyond the binary opposition between colonialism and nationalism. I am performing an exercise that I assign to my students when I teach the “Introduction to Critical Theory” course at the University of Miami. Instead of writing an essay with a short theoretical introduction followed by a detailed close reading of literary and cultural texts that illustrate a keyword or a theoretical insight, I conduct a methodological meditation in which I theorize the archipelagic as a form of relationality that configures an erotic imaginary beyond the nuclear family and towards affective networks. To think about the Caribbean as an archipelagic formation, I use my comparative work on the Antillean Confederation in the Hispanic Caribbean (1860-1898) and the West Indies Federation in the English Caribbean (1958-1962) as a historical context in which the region congealed as a network of locations “act[ing] in concert."